Implementation of Buerger Allen Exercises on Foot Sensitivity in Patients with Diabetes Mellitus - Susiana, Susiana; Faizal, Kgs. M; Fitri, Nurwijaya (Inspirasi Foundation, 2026)
Introduction: Diabetes mellitus is a chronic metabolic disease with a rapidly increasing global prevalence and is commonly associated with peripheral complications, including decreased foot sensitivity. Impaired peripheral circulation in patients with type 2 diabetes mellitus increases the risk of foot ulcers and other serious complications. Buerger Allen exercise is a non-pharmacological intervention that may improve peripheral blood flow and foot sensitivity through postural changes and muscle contractions. Therefore, this study aims to examine the effect of Buerger Allen exercise on foot sensitivity in patients with diabetes mellitus. Objective: This study aimed to evaluate the effectiveness of Buerger Allen Exercise in improving foot sensitivity among patients with Diabetes Mellitus at Sejiran Setason Regional Public Hospital, West Bangka, in 2025. Method: The study used a quantitative design with a quasi-experimental method, employing a pretest-posttest control group design with a total sample of 36 participants. The research involved two groups: an intervention group and a control group. Foot sensitivity was measured using the monofilament test before and after the intervention. The Buerger Allen Exercise therapy was carried out for five consecutive days, twice daily in the morning and afternoon. Result: The results showed a significant difference in foot sensitivity levels after the intervention in the treatment group (p-value = 0.00; p < 0.05). This indicates that Buerger Allen Exercise is effective in improving foot sensitivity in Diabetes Mellitus patients. Conclusion: It is recommended that this therapy be included as one of the nursing interventions in the management of Diabetes Mellitus at Sejiran Setason Regional Public Hospital, West Bangka.